1990
DOI: 10.1210/endo-127-1-264
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of a Novel Hypothalamic Peptide, Pituitary Adenylate Cyclase-Activating Polypeptide, in the Ovine Hypothalamus*

Abstract: We recently reported isolation, characterization and synthesis of a novel ovine hypothalamic peptide with 38 residues which stimulates accumulation of cAMP in rat anterior pituitary cell cultures. The peptide was named PACAP38 (pituitary adenylate cyclase-activating polypeptide with 38 residues). The presence of another peptide corresponding to the N-terminal 1-27 residues (PACAP27) was also demonstrated. Both PACAP38 and PACAP27 have an amidated C-terminus. Antisera against synthetic PACAP27 were generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(103 citation statements)
references
References 16 publications
6
97
0
Order By: Relevance
“…9,40 For instance, it has been suggested that they act as hypothalamic hormones controlling anterior pituitary cell function. In support of this notion is the demonstration of PACAP-and VIP-immunoreactive neurons within the median eminence 41,42 and specific binding sites for PACAP have been found on anterior pituitary cell membranes. 43 To date, only a few studies of PVRs in human pituitary adenomas have been published.…”
Section: Discussionmentioning
confidence: 86%
“…9,40 For instance, it has been suggested that they act as hypothalamic hormones controlling anterior pituitary cell function. In support of this notion is the demonstration of PACAP-and VIP-immunoreactive neurons within the median eminence 41,42 and specific binding sites for PACAP have been found on anterior pituitary cell membranes. 43 To date, only a few studies of PVRs in human pituitary adenomas have been published.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that PACAP 38 stimulates the adenylate cyclase activity of rat pituitary cells and increases intracellular cAMP at least 1,000 times more than does VIP (Miyata et al 1989). PACAP-like immunoreactivity (LI) has been immunohistochemically localized in nerve fibers and terminals distributed to the median eminence and pituitary stalk, suggesting a neurotransmitter, neuromodulator , or neurohormonal role for this peptide (Koves et al 1990).…”
mentioning
confidence: 99%
“…The peptide belongs to the secretin/glucagon/vasoactive intestinal peptide (VIP) family and shows the highest similarity (68%) to VIP. PACAP is widely distributed in mammalians with the highest concentration in the central nervous system (Koves et al, 1990;Arimura et al, 1991). It is a hypophysiotropic hormone and also functions as neurotransmitter, neuromodulator, and neurotrophic factor in the central nervous system (for details see the following reviews : Arimura et al, 1994;Arimura and Shioda, 1995).…”
mentioning
confidence: 99%